2017
DOI: 10.5114/jcb.2017.66082
|View full text |Cite
|
Sign up to set email alerts
|

Isobio software: biological dose distribution and biological dose volume histogram from physical dose conversion using linear-quadratic-linear model

Abstract: PurposeTo develop an in-house software program that is able to calculate and generate the biological dose distribution and biological dose volume histogram by physical dose conversion using the linear-quadratic-linear (LQL) model.Material and methodsThe Isobio software was developed using MATLAB version 2014b to calculate and generate the biological dose distribution and biological dose volume histograms. The physical dose from each voxel in treatment planning was extracted through Computational Environment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Jaikuna et al reported that it is useful to use the LQL model for the dose evaluation of radiotherapy in which the dose per fraction is high, such as in HDR brachytherapy and stereotactic radiation therapy, that the LQ model cannot be used. [24] Their report supports the propriety of our dose evaluation method.…”
Section: Discussionsupporting
confidence: 67%
“…Jaikuna et al reported that it is useful to use the LQL model for the dose evaluation of radiotherapy in which the dose per fraction is high, such as in HDR brachytherapy and stereotactic radiation therapy, that the LQ model cannot be used. [24] Their report supports the propriety of our dose evaluation method.…”
Section: Discussionsupporting
confidence: 67%
“…17 Another field for further development of dose constraints (even for normofractionated radio-therapy) would be taking into account the number of fractions and calculating dose constraints with equivalent dose 2 Gy (EQD2) correction. This strategy would allow for better comparison of dose constraints and side effects between different radiotherapy fractionation schedules as reported by Jaikuna et al 28…”
Section: Discussionmentioning
confidence: 99%
“…This strategy would allow for better comparison of dose constraints and side effects between different radiotherapy fractionation schedules as reported by Jaikuna et al . 28 …”
Section: Discussionmentioning
confidence: 99%